The Marketing Strategy of the Product with Sensual Marketing Reviewed from Islamic Perspective - Aditya, Fajar (International Journal of Islamic Business and Economics (IJIBEC), 2018)
There are many SPG who dress un-accordingly to the teachings of Islam when they are running product promoton actvites. This study uses qualitatve research method with a phenomenological approach. Subjectsin this study were women who worked as SPG, while the research object was in Semarang City. The results of this study indicates that the use of Sales Promoton Girl is potental to violate Islamic Sharia because of theinadequacy of the clothes used by SPG, since in the marketng system, the clothes used by Sales Promoton Girl are considerate un-accordingly to the provisions of the islamic sharia or not in accordance with the Islamic perspective.